Fibroblast growth factor-2-induced cardioprotection against myocardial infarction occurs via the interplay between nitric oxide, protein kinase signaling, and ATP-sensitive potassium channels - MANNING, JANET R. (Growth Factors, 2012)
Fibroblast growth factor-2 (FGF2) protects the heart from ischemia–reperfusion (I-R) injury via a vast network of protein kinases. In the heart, downstream effectors of these FGF2-triggered signals have not yet been identified. It is hypothesized that nitric oxide (NO) signaling and ATP-sensitive potassium (K(ATP)) channel activity are key effectors of protein kinases activated by FGF2-mediated cardioprotection. Hearts with a cardiac-specific overexpression of FGF2 (FGF2 Tg) were subjected to I-R injury in the absence or the presence of selective inhibitors of NO synthase (NOS) isoforms or sarcolemmal (sarcK(ATP)) and mitochondrial (mitoK(ATP)) K(ATP) channels. Multiple NOS isoforms are necessary for FGF2-mediated cardioprotection, and nitrite levels are significantly reduced in FGF2 Tg hearts upon inhibition of protein kinase C or mitogen-activated protein kinases. Likewise, sarcK(ATP) and mitoK(ATP) channels are important for cardioprotection elicited by endogenous FGF2. These findings suggest that FGF2-induced cardioprotection occurs via protein kinase-NOS pathways as well as K(ATP) channel activity.